PENGARUH LATIHAN HOLLOW SPRINT TERHADAP KECEPATAN ATLET SEPAKBOLA BINTANG TIMUR FOOTBAL CLUB PULAUBATU KECAMATAN JUJUHAN ILIR KABUPATEN BUNGO - Muhammad Ulfi; Hastria Effendi; Anton Komaini (JURNAL STAMINA, 2019)
The problem in this study was the lack of speed athletes of bintang timur fc pulaubatu, jujuhan ilir district, bungo regency. This study aims to increase the speed athletes of Bintang Timur Fc Pulaubatu, Jujuhan Ilir district, Bungo regency. This type of research is a quasi-experimental, the population in this study was Bintang Timur Fc athletes Pulaubatu, Jujuhan Ilir district, Bungo regency. Sampling uses purposive sampling technique, the instrument used in this study was a speed test using a 60 meter run test. The technical analysis of the data used in this study uses the t-test. The results of data processing in this study are tcount> t table = 28.85> 1.78, The results of this study prove that there is a significant (increasing) effect of giving hollow sprint training to the speed of Soccer Athletes Bintang Timur FcPulaubatu Jujuhan Ilir District, Bungo Regency. meaning that the treatment of the applied hollow sprint exercises the author can improve the ability of speed. So that the hollow sprint exercises applied by the author can be used in the training process